Relationship between oral health literacy and oral health status - Jagan Kumar Baskaradoss (BMC, 2018)
Abstract Background Health literacy has been found to be a strong predictor of an individuals' health, health behavior and health outcomes. Lower literacy has been linked to problems with the use of preventive services, delayed diagnoses of medical conditions, poor adherence to medical instructions, poor self-management skills, increased mortality risks, poor health outcomes, and higher health care costs. The aim of this study is to determine the relationship between oral health literacy (OHL) and oral health status among patients attending a University-affiliated dental clinic. Methods A convenience sample of participants was drawn from the dental patients presenting at School of Dental Medicine (SODM), Case Western Reserve University (CWRU). Information about the subjects' demographic details, income, family size, insurance type and smoking history were collected using a data collection form. Data about the patients' periodontal and caries risk assessment, caries experience and periodontal status was extracted from the patients' electronic dental records. The Comprehensive Measure of Oral Health Knowledge (CMOHK) was used to record the oral health literacy. The median CMOHK score was 18, and this was used to categorize the sample into limited OHL (≤18) and adequate OHL (> 18) groups. A multivariate logistic regression model was built to examine the associations between the various independent variables and OHL levels. Results Data of 150 respondents were analyzed. More than half of the participants were female (55.3%) and the majority were Caucasian (60%). The average age of participants was 53.3 years [standard deviation (SD) 16.8]. Higher percentage of African Americans and individuals with low education had limited OHL levels (p < 0.05). The mean decayed, missing, and filled teeth (DMFT) score for this population was 7.33 ± 2.68. Subjects with limited OHL had significantly higher mean values for missing teeth (p < 0.05) and lower mean values for filled teeth (p < 0.05) as compared with subjects with adequate OHL Significantly, higher percentage of subjects with limited OHL had severe periodontitis as compared with those with adequate OHL (p = 0.04). Multivariate analysis found that the periodontal status was significantly associated with the OHL scores (p = 0.015). Conclusion Subjects with limited OHL levels had poorer periodontal health. Improving the OHL of patients may help in the efforts to improve the adherence to medical instructions, self-management skills and the overall treatment outcomes. Future research could focus on assessing the impact of OHL interventions on the oral health, which could be valuable for clinical practitioners.